Design and Construction of a Voice Control System for Appliances Using Android Via Bluetooth. - Twizerimana Daniel (Kabale University, 2023)
This Project report represents/shows a detailed system of controlling appliances using voice commands. The most common method of controlling appliances is by pressing the switches manually and this becomes very difficult for the elderly or physically handicapped people. This system is a solution to such problems. Bluetooth is interfaced to the arduino board using the transmitter and receiver pins for communication. The electrical loads are controlled by the relay which is connected to the arduino board, so the respective devices and appliances are turned on or off depending on the voice command. This system is cheap, affordable and easy to use unlike the current systems which are not well embraced due to complexity, high costs and multiple incompatible standards.